Find the zeros of the function.
Write the smaller solution first, and the larger solution second.
h(x) = (-2x+3)(-x+3)
smaller x=
larger x=

Respuesta :

Answer:

smaller x= 3/2

larger x= 3

Step-by-step explanation:

For any two expressions A and B:

If A x B=0  then either A=0 or B=0.

This is called the zero product property.

Hint #22 / 3

In our case, (-2x +3)(-x +3)=0(−2x+3)(−x+3)=0

So either (-2x +3)=0(−2x+3)=0 or (-x +3)=0

(1)     −2x+3 =0

−2x  = -3

x= 3/2

(2) ​    −x+3 =0

-x=-3

x=3

In conclusion,  

smaller x  = 3/2

larger x  = 3